Pergesaran Budaya Pada Sistem Kemasyarakatan Komunitas Adat (Jurnal Pembangunan Sosial, 2018)
The cultural shift in a community or traditional community will have an impact on the changing characteristics or identity of the indigenous community. This study aims to obtain an overview of shifts or changes in aspects of culture in Sedulur Sikep Samin Karangpace Traditional Community. One aspect of culture studied was the aspect of the social system. The research was conducted using a qualitative approach through descriptive methods, with 7 informants. The results showed that cultural shifts in the aspects of the social system experienced considerable changes, this was marked by changes in the rules and procedures of marriage that had followed the rules of the country, manners that began to change, especially in children, but in terms of kinship terms and permanent kinship as before that is family.